Utilizing Rapid Molecular Tests (RMT/RIF) in Tuberculosis Drug-Sensitive/Resistant Discovery in Indonesia: A Pilot Study - Herawati, Maria Holly; Dasuki, Dasuki; Lolong, Dina Bisara; Widiyanti, Mirna; Roosihermiatie, Betty; Permata, Ria Yuda; Raflizar, Raflizar; Ahmadi, Ferry; Supratikta, Hadi; Veruswati, Meita (UI Scholars Hub, 2023)
The underdiagnosis and underreporting of tuberculosis (TB) indicators are unresolved problems. The rapid molecular test (RMT) is one of the breakthroughs for TB case finding by using safer and more sensitive equipment; it is even believed to help find drug-resistant TB. The results of several webinars held regularly by a TB program as well as its evaluation and the use of RMT formed the basis of this study. This initial pilot study aimed to provide an overview of case finding for both drug-sensitive and drug-resistant TB using RMT. A cross-sectional study was conducted on samples in several provinces in Indonesia that have used RMT, both in remote or non-remote island borders areas and fiscal capacity. Regarding the use of RMT for drug-sensitive TB case finding, the largest contributors were males aged above 15 years, while in the drug-resistant TB case finding group, the biggest contributor was the use of RMT in 2017 and 2018. Overall, the findings could only describe the situation in the study area. The use of RMT in drug-sensitive TB case finding would be maximized if the detected cases are males aged above 15 years, while RMT can help find cases of drug-resistant TB.